Identifying an emergent adulterant hydrochlorothiazide in food: A simple lateral flow strip with high sensitivity by time-resolved fluorescence. (January 2023) - Shen, Runlin; Guan, Tian; Li, Zhaodong; Hong, Ziling; Dzantiev, Boris B.; Zherdev, Anatoly V.; Koidis, Anastasios; Yao, Xiaojun; Lei, Hongtao
Abstract: Hydrochlorothiazide, an antihypertensive and diuretic drug only for clinic purpose, was recently found as an adulterant in functional foods. Due to the potential health risk, it is urgent to develop a simple and rapid assay for its identification. In this work, two hapten structures were rationally designed based on molecular modeling, and a highly sensitive antibody to hydrochlorothiazide was obtained with 50% inhibitive concentration (IC50 ) of 6.7 ng/mL for the first time. A lateral flow strip assay was then developed based on time resolved fluorescence, demonstrating a cut-off value of 250 μg/kg to hydrochlorothiazide in functional capsules and tablets, and a negligible cross-reactivity to related compounds. The strip performance for real samples collected from the retail markets was consistent of that of confirmed method (LC-MS/MS). As an ideal tool, the proposed strip could be applied to identify adulterated hydrochlorothiazide in functional foods. Graphical abstract: Image 1 Highlights: Two novel hydrochlorothiazide haptens were rationally designed assisted by computer molecular modeling. A novel antibody against hydrochlorothiazide was produced with high specificity and sensitivity. A easy-use lateral flow strip was developed for identifying emergent adulterant hydrochlorothiazide in foods.